The Role of IL-6 Released During Exercise to Insulin Sensitivity and Muscle Hypertrophy - de Melo Madureira, Álvaro Nóbrega; de Oliveira, João Ricardhis S.; de Menezes Lima, Vera Lúcia (Mini Reviews in Medicinal Chemistry, 2022)
Interleukin-6 (IL-6) influences both inflammatory response and anti-inflammatory processes. This cytokine can be released by exercising skeletal muscle, which characterizes it as a myokine. Unlike what is observed in inflammation, IL-6 produced by skeletal muscle is not preceded by the release of other pro-inflammatory cytokines, but it seems to be dependent on the lactate produced during exercise, thus causing different effects from those seen in inflammatory state. After binding to its receptor, myokine IL-6 activates the PI3K-Akt pathway. One consequence of this upregulation is the potentiation of insulin signaling, which enhances insulin sensitivity. IL-6 increases GLUT-4 vesicle mobilization to the muscle cell periphery, increasing the glucose transport into the cell, and also glycogen synthesis. Muscle glycogen provides energy for ATP resynthesis, and regulates Ca2+ release by the sarcoplasmic reticulum, influencing muscle contraction, and, hence, muscle function by multiple pathways. Another implication for the upregulation of the PI3K-Akt pathway is the activation of mTORC1, which regulates mRNA translational efficiency by regulating translation machinery, and translational capacity by inducing ribosomal biogenesis. Thus, IL-6 may contribute to skeletal muscle hypertrophy and function by increasing contractile protein synthesis.
Keywords: TNF-α